Definiranje upoštevnega trga po uvedbi ekonomskega orodja za ugotavljanje konkurenčnega pritiska na zvišanje cen - Repinc, Tjaša (Podjetje in delo, 2014)
The author advocates that the market definition in the USA preserves its prominent role despite both, the change of the American Horizontal Merger Guidelines on defining relevant market in 2010 and the introduction of economic tool Upward Pricing Pressure (UPP). The latter is strictly reserved for the assessment of the unilateral effect only in the case of merger involving differentiated products. European Commission has not followed the USA in changing its Guidelines on the assessment of horizontal mergers due to adequate legal basis for the UPP in its paragraphs 24 and 28. So far, the UPP has been applied in two merger cases, Hutchison 3G (H3G)/Orange Austria and UPS/TNT Express. In future, European Commission's decisions might affect the Slovenian Competition Protection Agency`s assessment of concentration particularly in similar cases as the ones mentioned.
Keywords: cene; konkurenca; podjetja; združevanje